2019
DOI: 10.21608/ejnf.2019.103456
|View full text |Cite
|
Sign up to set email alerts
|

Replacement Corn Silage by Orange Waste Silage in Barki Ram Lambs Rations

Abstract: he present work was conducted to study the effect of replacement corn silage (CS) by orange waste silage (OR) improved the performance of Barki lambs using one of the following rations: R1: 50% concentrate feed mixture (CFM) + 40% corn silage (CS) + 10% rice straw (RS) (control). R2: 50% CFM + 20% CS + 20% orange waste silage (OS) + 10% RS and R3: 50% CFM + 40% OS + 10% RS. Two experimental trials were conducted: Results showed the silages had good smell and were free from any signs of molds in all groups. Dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
3
3
1
Order By: Relevance
“…The replacement of maize silage by orange byproducts silage at 50% or 100% in G2 and G3 had significantly affected all nutrient digestibility coefficients compared with maize-silage based diet(G1). These results were in agreement with Mahrous et al (2019); Shdaifat et al (2013); and Gholizadeh and Naserian. ( 2010) who reported that DM, OM, CP and CF digestibility were increased when dried citrus pulp substitute for starchy feeds.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The replacement of maize silage by orange byproducts silage at 50% or 100% in G2 and G3 had significantly affected all nutrient digestibility coefficients compared with maize-silage based diet(G1). These results were in agreement with Mahrous et al (2019); Shdaifat et al (2013); and Gholizadeh and Naserian. ( 2010) who reported that DM, OM, CP and CF digestibility were increased when dried citrus pulp substitute for starchy feeds.…”
Section: Resultssupporting
confidence: 90%
“…In this respect, Omer and Tawila (2009) concluded that replacements of corn grains by citrus by-production in goat's ration improved feed efficiency and decreased daily feeding cost, and consequently improved relative economic efficiency. Similarly, Mahrous et al (2019) found that all rations containing citrus byproduct silage recorded the best feed conversion values compared with corn silage in growing Barki lambs.…”
Section: Resultsmentioning
confidence: 80%
“…The values of CF and EE in OPS was in agreement with [20] who showed that their contents in OPS were 17.96 and 3.73%, in the same order. Our findings for DM, CP and CF were noticed to be lower than those observed by [19] who recorded their values to be 38.90, 8.72, and 28.56%, respectively. The NDF and ADF values for CS were higher than those for OPS (41.3 and 29.45% vs. 34.6 and 22.89%, respectively).…”
Section: Chemical Composition Of Feeds and Experimental Rationscontrasting
confidence: 93%
“…Hemicellulose content in OPS was similar to that of CS (11.71 vs. 11.85%). The current result was near to that noted by [19] who recorded10.15-10.8% hemicellulose in OPS. On contrary, the cellulose content of CS was higher than its content in OPS (24.62 vs. 17.83%).…”
Section: Chemical Composition Of Feeds and Experimental Rationssupporting
confidence: 85%
See 1 more Smart Citation